Synergizing Transformational, Democratic, and Spiritual Leadership: A Triadic Approach to Enhancing Educational Quality in Islamic Schools - Herna Wati; Siti Raudhatul Jannah; Atika Atika (JURNAL AL-TANZIM, 2026)
This study aims to analyze Madrasah Principal Leadership Styles in Enhancing Educational Quality: A Case Study at MTs Pondok Pesantren Nurul Iman Seberang, Jambi. The research employs a qualitative approach with a case study design to gain an in-depth understanding of leadership practices within their natural context. Data were collected through in-depth interviews, participant observation, and documentation, involving the principal, teachers, and staff as key informants. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the principal implements an integrated leadership style combining transformational, democratic, and spiritual approaches. Transformational leadership is reflected in motivating teachers and encouraging professional development, while democratic leadership fosters participation and collaborative decision-making. Meanwhile, spiritual leadership reinforces moral values and promotes a religious-based organizational culture. This integrated approach contributes significantly to improving educational quality, including enhanced teacher performance, a supportive learning environment, and strengthened character education.